Pengawasan Dana Bantuan Operasional Sekolah (BOS) untuk Sekolah Dasar (SD) di Dinas Pendidikan Kabupaten Temanggung - Anisa Rahayu; Endang Larasati Setianingsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
School Operational Assistance is the government’s program to provide non-personalia operational fund for elementary school as the practitioner of the compulsory education. This research aims to describe and analyze the practice of controlling the School Operational Assistance in Elementary School in Education Board of Temanggung Regency and to identify factors contributing the control of the School Operational Assistance. This research used descriptive qualitative method. The result shows the practice of School Operational Assistance has been going on well based on the control. The factors contributing in the controlling of School Operational Assistance in Elementary School are the change of organization’s environment, improvement of organization’s complexity, errors and manager’s necessary to delegate authority. The control of School Operational Assistance in Elementary School in Education Board of Temanggung Regency need to be improved to minimize errors and increase comprehension of the Technical Instructions. Practitioner time management improvement is needed to increase teamwork in controlling process and meeting schedule for development can be fulfilled in a year.